Mudança no âmbito organizacional: o poder preditivo dos valores organizacionais - Slivnik, Maximiliano Liubomir (2016)
In the current competitive world, organizational change plays a relevant role in the sustainable survival of organizations. The Social Sciences literature analyses the various factors that influence organizational change, which involves people, structures, strategies, processes and timing. Among these factors, organizational values are principles and beliefs, hierarchically organized according to desirable organizational behaviors and goals. This work pretends identify the predictive power of organizational values for understanding change within organizations. A descriptive, transversal, quantitative research was done with 183 employees of one organization in the Brazilian food industry, represented in many states of the country. The organization had been through a top-down and planned organizational change. Interviewees were asked to fill a questionnaire divided in four parts organizational values; attitudes facing change; perception of individual change; and perception of organizational change. The data was treated with descriptive and inferential analysis. The results show that the value Autonomy is a relevant predictor for all the factors of organizational change. The same result was obtained for the attitude Acceptance and Fear of change. The data also show that, when organizational values and attitudes are taken as a single statistic variable, the perceived factors of organizational change Pursuit of Results, Technical Competence and Welfare are explained by the organizational value Autonomy; the factors Horizontality, Participation and External Image are explained by the attitude Acceptance.